Peningkatan Daya Saing Kelompok UMKM Penjahit melalui Pendampingan Digitalisasi Marketing Berbasis Aplikasi Mobile Tailor Fashion di Surabaya - Widyastuti, Rahma; Setiawan, Adhar Putra; Gunawan, Gunawan; Hakim, Lukman; Rohman, M. Taufiqur (Jurnal SOLMA, 2026)
Background: Strategies to Increase Competitiveness and Marketing Patterns of Rini Collection Tailor MSMEs in Kejawan Putih Tambak Surabaya Effectively and Efficiently. This study aims to enhance the competitiveness and governance of Rini Collection Tailor MSMEs by leveraging Information Technology, such as Social Media and Applications, and Tailor Fashion Websites, with a case study of Rini Collection Tailor MSMEs in Kejawan Putih, Tambak, Surabaya. Method: Research Methods 1) Socialization or identifying MSME needs analysis 2) Creation and Management of Applications and Tailor Fashion Websites 3) Digital Literacy Training, Use of Social Media and Applications and Tailor Fashion Websites 4) Mentoring and Periodic Evaluation 5) Program Sustainability. Results: After mentoring and training, the implementation of strategies using social media and applications, and Tailor Fashion websites, has resulted in a significant increase in the number of new customers and in profits. The success of the Rini Collection Tailor MSME Group can be linked to the use of Information Technology, or IPTEK, to leverage social media effectively and efficiently. The visual display of products on the Fashion Tailor Application and Website can attract interest, as well as direct communication with customers through the Digital Platform. Conclusion: The Implementation of Social Media and Fashion Tailor Applications and Websites has been proven to improve marketing reach and increase profit for the Rini Collection Tailor MSME. Although there are still challenges in adapting to the information technology digital Era.